Modified One Man Beach Profiling Method - Bryant, Edward (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1979)
A vapid one-man, beach profiling method is presented. The scheme ie based upon a 1.5 x l.S-m H-shaped frame and uses the earth's horizon as a level. A small correction must be applied to readings to correct for the Earth's curvature. Measurement error in the method decreases with increased packing of sediment but is independent of grain size. Profiles plotted using this scheme are replicable and similar in slope and shape to ones surveyed using instrument levelling.